Diffusivity and resistance to deterioration from freezing and thawing of binary and ternary concrete mixture blends - Beck, Lisa Elanna (Kansas State University, 2011)
Corrosion of reinforcing steel is one of the most common and serious causes of reinforced concrete deterioration. While corrosion is normally inhibited by a passive layer that develops around the reinforcing steel due to the high pH environment of the surrounding concrete, chlorides will break down this protective layer, leading to reinforcement corrosion. Decreasing the diffusivity of the concrete would slow the ingress of chlorides into concrete, and is one of the most economical ways to increase the concrete service life. Optimized concrete mixtures blending portland cement and supplementary cementing materials (SCMs) have become popular throughout the construction industry as a method of improving both fresh and long-term concrete properties such as workability, strength and porosity. It has been shown that use of Class F fly ash, silica fume and ground granulated blast furnace slag (GGBFS) in binary concrete mixture blends can result in a significant reduction in concrete diffusivity. This study investigates the ability of Class C fly ash and ternary concrete mixture blends to also aid in diffusivity reduction. In order to study the effect of incorporation of SCMs into concrete, mixtures containing Class C and Class F fly ash, silica fume and GGBFS were tested following the ASTM C 1556 procedures to measure the concrete’s apparent chloride diffusivity. Structure life cycles were modeled using the measured apparent chloride diffusivities with two finite-difference based life-cycle analysis software packages. To determine whether a correlation between diffusivity and deterioration due to freezing and thawing exists, samples were also tested for their ability to resist deterioration from freezing and thawing cycles using a modified ASTM C 666 Procedure B test. Results show that the use of Class C fly ash yields some service life improvements as compared to the portland cement control mixtures, while ternary mixture blends performed significantly better than the control mixture and equal to or better than the binary SCM mixtures tested. Freeze-thaw tests showed all mixtures to be equally resistant to deterioration due to freezing and thawing.
Keywords: Concrete; Diffusivity; Freeze-thaw durability; Ternary mixture blends; Class C fly ash; Service life modeling; Civil Engineering (0543)